Thailand Seeking to Re-engage Myanmar Junta with Asean: National Interest or Political Ambition? - Masri, Sylvia; Anwar, Syaiful; Surjaatmadja, Surachman (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The government of Thailand under Prime Minister Prayuth Chan-o-cha hosted an informal meeting to have a discussion on Myanmar in Pattaya, 18-19 June 2023. The invitation was rejected by Indonesia, Malaysia, and Singapore because the meeting disagrees with the ASEAN's Five-Point Consensus issued to respond to Myanmar military coup d’etat in February 2021 and its after-effects. Apart from Thai Foreign Minister, only a few officials at a minister level attended the gathering, including Myanmar Foreign Minister, Than Swe; and Lao Foreign Minister, Saleumxay Kommasith. Brunei Darussalam, Cambodia, Vietnam, and the Philippines sent their representatives; and India and China were also present. Thailand defended its move, emphasizing that direct talks with Myanmar were necessary to protect Thailand because its territorial proximity with Myanmar had been creating refugee and border problems, and affecting badly their bilateral trade. The research seeks to explain whether Thailand promoting re-engagement between Myanmar junta and ASEAN is only based on the national interests of the country or there are other influencing factors, by focusing on Prime Minister Prayuth Chan-o-cha’s political track record and Thailand’s foreign policy under his government; and referring to hedging strategy. The research finds that the policy to re-engage Myanmar junta with ASEAN was influenced by the Prime Minister’s political interest, along with the need for Thailand to protect its national interests. Omnidirectional hedging strategy, in its relations with the US, China, and regional power house such as India, helps as well to explain the move Thailand made with regards to Myanmar and ASEAN.